1984
DOI: 10.1111/j.1365-2842.1984.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mandibular dysfunction in 10–18 year old Israeli schoolchildren

Abstract: The prevalence of mandibular dysfunction in a sample of 369 Israeli schoolchildren was found to be 56.4%, indicating that one or more of the cardinal symptoms were present. It increased with age from about 51% in the 10-13 year old group to 67.8% in the 16-18 year olds. The most common cardinal sign of dysfunction was joint sounds (35.8%), which increased with age from 28% in the youngest group to 44.3% in the oldest group. The second most common sign was joint sensitivity to palpation (30.4%), which showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
5
4

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 9 publications
4
37
5
4
Order By: Relevance
“…Such findings are not unusual. In a study on 10-to 18-year-old children and adolescents in Israel, the authors observed up to 5 mm of difference in jaw opening between girls and boys [14]. We cannot explain such differences because we did not measure potential causal factors (such as greater height or longer mandibles in boys) in this study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Such findings are not unusual. In a study on 10-to 18-year-old children and adolescents in Israel, the authors observed up to 5 mm of difference in jaw opening between girls and boys [14]. We cannot explain such differences because we did not measure potential causal factors (such as greater height or longer mandibles in boys) in this study.…”
Section: Discussionmentioning
confidence: 69%
“…Solche Befunde sind nicht ungewöhnlich. In einer Studie an 10-bis 18-jährigen Kindern und Jugendlichen in Israel wurden bis zu 5 mm Unterschied zwischen Mädchen und Jungen bei der Kieferöffnung gefunden [14]. Wir können diese Differenzen nicht erklären, da potenzielle ursächliche Faktoren wie stär-keres Körperwachstum oder größere Unterkieferlänge bei Jungen in der vorliegenden Studie nicht bestimmt wurden, was als Limitation angesehen werden muss.…”
Section: Discussionunclassified
“…The prevalence of temporomandibular joint dysfunction (TMD) in the adolescent population has been reported previously and varies considerably depending on the sample selection, the criteria used to define disc displacement, and the type of study conducted [21][22][23]. It has been widely reported in the literature [24,25] that TMD is more common in females than in males, and females exhibit more defined signs than males [26].…”
Section: Discussionmentioning
confidence: 94%
“…Their incidence has been reported as being between 6% and 68% in previous studies 1-5. Radiographic examination may serve to provide additional information along with clinical findings.…”
Section: Introductionmentioning
confidence: 91%